Symbols and Connotations in The Art of Islamic Architecture - SEGHIRI, Racha Ouissal (Journal of Human Sciences, 2025)
The art of Islamic architecture is distinctive and unique in nature because it uses the language of symbols and suggestions as a means of expressing the abstraction of the form, the hint of meaning and the remoteness of the statement, due to specific religious and ideological reasons, and the inheritance of this symbolic thought across various time hurdles to this day. So through this study we will try to identify these symbols and reveal their connotations and interpret them by linking them with Islamic thought.